The Effect of Profitability and Liquidity on the Value of Infrastructure Sector Companies on the Indonesia Stock Exchange for the 2014-2023 Period - Suyono, Aji Prasetyo; Chandra, Yulian Ade; Kinanti, Kartika Ayu (Jurnal Ilmu Manajemen Advantage, 2024)
The impact of infrastructure development over the past ten years should have begun to be felt by the community, which is expected to increase company profits and attract investors to make investments. This study aims to determine investment opportunities for companies listed on the Stock Exchange of Indonesia. The data to be processed is ratio data consisting of ROE, Cash Ratio, and Value Ratio from five infrastructure sector companies that are at least one decade old and are included in the Main Board category, namely issuers that are large companies and have a good financial track record. The research methodology is quantitative and makes use of SEM PLS. The study's findings indicate that although the profitability ratio and profitability ratio have increased, this only has a small effect on the Company's Valuation. Therefore, investors should not only focus on paying attention to the company's financial ratios, but also need to pay attention to its business strategy in the future.